Predictive Factors of Successful Return to Work Following Discectomy. Issue 4 (May 2022) - Andersen, Mikkel Ø.; Ernst, Carsten; Rasmussen, Jesper; Ankjær, Thomas; Carreon, Leah Y.
Study Design: Retrospective analysis of prospectively collected data. Objective: To identify modifiable factors associated with successful return to work 12 weeks following discectomy. Lumbar disc herniation is a common cause of sciatica and sick leave. This presents an economic burden to the individual and the society. Methods: Data from DaneSpine on a consecutive cohort of patients operated due to lumbar disc herniation during a 3-year period was identified and merged with data from the Ministry of Employment's register on public welfare payments. Data on welfare payments 2 years prior to the date of operation and 1 year postoperative was included. Patients were considered to be on sick leave if they received welfare payments for the week. Patients are considered to have returned to work if they did not receive public welfare payments for a 4-week period. Results: Of 1134 patients meeting inclusion criteria, 98.5% had complete preoperative surgical data available. Postoperatively, 79.1% of the patients returned to the work within 12 weeks. Physically demanding jobs, low preoperative EQ5D score, and long duration of sick leave prior to surgery were associated negatively with return to work at 12 weeks. Conclusion: The results of this study indicate that patients who have a longer duration of sick leave have a physically demanding job and are in a poor health are more likely not to return to work by 12 weeks after surgery for lumbar disc herniation. Future studies are needed to determine if earlier referral to a surgeon leads to an earlier return to work.